The Development of Augmented Reality in Chemistry Laboratory Course to enhance Undergraduate Students’ Learning Achievement - Prasertsung, Nuttapong; Songsriwittaya, Alisa; Rungsirisakun, Ratana (Journal of Information and Learning [JIL], 2022)
This study aimed 1) to develop augmented reality in chemistry laboratory course with the efficiency of 80/80 and 2) to compare achievement score with pre-test score of students who studied via augmented reality in chemistry laboratory course. Participants were selected by purposive sampling. They were 137 first year engineering students from the Faculty of Engineering at King Mongkut's University of Technology Thonburi in Ratchaburi. The research tools comprised 1) the augmented reality in chemistry laboratory course, 2) achievement tests, and 3) a questionnaire to evaluate students’ satisfaction. Data were analyzed by using average percentage standard deviation statistics and t–test dependent. The research revealed that the efficiency of the augmented reality in the chemistry laboratory course was 88.46/80.33. The students’ learning achievement after learning via augmented reality was higher at the .01 level of significance. The satisfaction of students towards augmented reality in the chemistry laboratory course was at a high level.